HUBUNGAN IKLIM ORGANISASI DENGAN MOTIVASI KERJA PEGAWAI BADAN PEMBERDAYAAN PEREMPUAN DAN KELUARGA BERENCANA PROVINSI SUMATERA BARAT - Sukri Ramadhani (Universitas Negeri Padang, 2014)
The goal of this research are to see information about the Organizational Climate Relationship with employed Motivation Work. The population is 46 employee and the sample is 44 people that taken by proporsional random sampling research. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score and performance level. The result of this research are the Organizational Climate Relationship with Motivation to Work in office kantor Badan Pemberdayaan Perempuan dan Keluarga Berencana Provinsi Sumatera Barat. Key word : Organizational Climate and Motivation work